A Technique for Better Energy Management of Single-Stage Topology of Stand-Alone Photovoltaic System - Abbas, Ghulam; Azeem, Omar; Murtaza, Ali Faisal; Tahir, Umair (International Journal of Integrated Engineering, 2020)
This paper proposes a technique for energy managing of a stand-alone photovoltaic system. The proposed system employs a power processing inverter, which contains high PV voltage at the input to mitigate the magnitude of AC signal at the output, eliminating use of DC-DC converter and reduces the input capacitor size of PV array. To meet the power requirement of load and to maintain the maximum power point operation of PV array, battery bank is utilized with a bi-directional converter. An impedance model of the complete system is executed. Based on the model, the control architecture is designed which works in four modes: 1) if load demands > MPP of PV, additional current is extracted from the battery; 2) if load demands < MPP of PV array, extra current is given to the battery; 3) only load management is utilized since the battery bank is not available because of over-charging or under-charging; 4) if irradiation varies then first mode is used for load requirement. The technique is designed which guarantees the maximum power point tracking of PV system even without using any intermediate stage of DC-DC converter, hence making it single-stage, MPPT is achieved by effectively controlling bi-directional converter used for battery charging and discharging purpose. To ensure better utilization of dc voltage enhanced efficiency and low less harmonic distortion, sinusoidal PWM technique is used to drive the inverter. Simulation results are carried out for ensuring better energy management along with MPPT operation demonstrated under uniform operating conditions.